Alapítói köszöntő a "Gerundium" Egyetemtörténeti Közlemények című folyóirat indításához - Fésüs, László (Gerundium, 2010)
Alapítói köszöntő a "Gerundium" Egyetemtörténeti Közlemények című folyóirat indításához